2019
DOI: 10.3390/cancers12010025
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials as Inhibitors of Epithelial Mesenchymal Transition in Cancer Treatment

Abstract: Epithelial-mesenchymal transition (EMT) has emerged as a key regulator of cell invasion and metastasis in cancers. Besides the acquisition of migratory/invasive abilities, the EMT process is tightly connected with the generation of cancer stem cells (CSCs), thus contributing to chemoresistance. However, although EMT represents a relevant therapeutic target for cancer treatment, its application in the clinic is still limited due to various reasons, including tumor-stage heterogeneity, molecular-cellular target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 228 publications
(285 reference statements)
0
22
1
Order By: Relevance
“…As previously known, among the three main different types of EMT (EMT on embryogenesis, EMT on chronic fibrotic pathologies, and EMT during tumor progression), the tumor-related EMT most often undergoes an incomplete or partial EMT. [27][28][29][30] We found different results from previous studies conducted by Xu et al in osteosarcoma MG-63 cells and Park et al in pancreatic cancer cells. Both studies showed that alpha mangostin suppressed EMT.…”
Section: The Effect Of Alpha Mangostin Alone or In Combination With Scontrasting
confidence: 95%
See 1 more Smart Citation
“…As previously known, among the three main different types of EMT (EMT on embryogenesis, EMT on chronic fibrotic pathologies, and EMT during tumor progression), the tumor-related EMT most often undergoes an incomplete or partial EMT. [27][28][29][30] We found different results from previous studies conducted by Xu et al in osteosarcoma MG-63 cells and Park et al in pancreatic cancer cells. Both studies showed that alpha mangostin suppressed EMT.…”
Section: The Effect Of Alpha Mangostin Alone or In Combination With Scontrasting
confidence: 95%
“…As previously known, among the three main different types of EMT (EMT on embryogenesis, EMT on chronic fibrotic pathologies, and EMT during tumor progression), the tumor-related EMT most often undergoes an incomplete or partial EMT. 27 - 30 …”
Section: Resultsmentioning
confidence: 99%
“…Molecularly, the EMT phenotypic switch is accompanied by downregulation of epithelial cell markers including E-cadherin and cytokeratin, and upregulation of mesenchymal markers such as vimentin, fibronectin, snails, and N-cadherin 1 , 2 . EMT is regulated by complex molecular pathways and multiple signaling events including TGFβ, WNT, MAPK, FAK and JAK/Stat, Hedgehog, and Hippo-YAP/TAZ 3 , 4 . Accumulating experimental evidence indicates that EMT contributes to tumor metastasis, chemoresistance, and immunosuppression 1 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Direct pharmacological inhibition of EMT transcription factors is difficult [68]. Alternative approaches to target EMT are described using metabolic inhibitors [69] or nanomaterials [70]. Examples include suramin for prostate cancer [71], inhibition of inducible nitric oxide synthase for triple negative breast cancer [72], and chitosan as a nanocarrier for SN38 and Snail-specific siRNA in prostate cancer cells [73].…”
Section: Discussionmentioning
confidence: 99%